2020
DOI: 10.1212/wnl.0000000000009979
|View full text |Cite
|
Sign up to set email alerts
|

Novel approaches to quantify CNS involvement in children with Pompe disease

Abstract: Objective:To characterize the extent of central nervous system involvement in children with Pompe disease using brain magnetic resonance imaging (MRI) and developmental assessments.Methods:The study included fourteen children (ages 6-18 years) with infantile Pompe disease (IPD) (n=12) or late onset Pompe disease (LOPD) (n=2) receiving enzyme replacement therapy. White matter (WM) hyperintense foci seen in the brain MRIs were systematically quantified using the Fazekas scale (FS) grading system with a novel app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Conventional magnetic resonance imaging (MRI) can identify some long-term changes of the central nervous tissue, such as morphologic local damage, brain atrophy, and alterations of WM [ 7 , 9 , 12 , 24 28 ]. The highest number of WM changes were seen in the cisplatin group, which is consistent with previous publications where medulloblastoma treatment exhibited a high risk of WM damage [ 7 , 9 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional magnetic resonance imaging (MRI) can identify some long-term changes of the central nervous tissue, such as morphologic local damage, brain atrophy, and alterations of WM [ 7 , 9 , 12 , 24 28 ]. The highest number of WM changes were seen in the cisplatin group, which is consistent with previous publications where medulloblastoma treatment exhibited a high risk of WM damage [ 7 , 9 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…FS was categorized according to the treatment-related parenchymal changes (0 none/single lesion; 1 multiple punctate; 2 beginning confluence of lesions; 3 large confluent lesions). When employing FS, we used the following methodologies [ 12 , 13 ]. The MRI studies included FLAIR sequences (slice thickness 4–5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with infantile-onset Pompe disease (IOPD) are now living longer since the advent of intravenous (ERT) [ 6 ]. Brain autopsies of untreated infants showed widespread glycogen storage in the CNS [ 29 ], but this therapy is unlikely to cross the blood–brain barrier, thus increasing concerns about long term effects on CNS [ 29 , 30 ]. Ebbink and Spiridigliozzi [ 29 ] suggested that, in children with GSD2 treated with ERT, despite the strong evidence of glycogen storages in the brain, the impact on CNS seems to be limited.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have identified disease impact in both the central and peripheral nervous systems of individuals with IOPD and LOPD [10][11][12][13][14][15]. Understanding clinical signs resulting from neurological and motor impairments, both individually and in combination with each other, are critical to refining our understanding of disease phenotype.…”
Section: Introductionmentioning
confidence: 99%